Prospective Randomized Study between Intravesical BCG and Mitomycin-C for Non-Muscle-Invasive Urothelial Carcinoma of Urinary-Bladder Post TURBT - Mondal, Hari Pada; Yirang, Kapang; Mukhopadhyay, Chandranath; Adhikary, Shyam Sundar; Dutta, Biswajit; Bhoj, Sudhansu Sekhar (Bangladesh Journal of Medical Science, 2016)
Background: Approximately 70% of urinary bladder cancer are non-muscle invasive at presentation. It is notorious for its high incidence and recurrence rate. The five-year recurrence rate varies between 30 and 60%. The intravesical treatment evolved out of need to prevent tumour recurrence after local surgical resection. Objectives: To compare intravesical Mitomycin C and BCG therapies in the prevention of recurrences and severity of their side effects. Materials and Methods: 40 patients with superficial bladder cancer were studied in urology unit of surgery department of North Bengal Medical College, Darjeeling from June, 2012 to May, 2013. They underwent transurethral resection of bladder tumour. Post operatively 19 patients were treated by intravesical Mitomycin C and 21 patients with BCG. Post intravesical therapy, patients were monitored 3 monthly for recurrence and side effects. Results: No recurrence was observed at the 3rd month follow up, two recurrences were observed at the end of 6th month in the Mitomycin C group. Regarding side effects, cystitis had no significant difference between the two groups but fever, hematuria and retention of urine were found significantly in BCG group during the study period. Conclusions: In the prevention of recurrences, intravesical Mitomycin C and BCG therapies have comparable efficacies at the end of 6 months. A further follow up period is required to see and compare the long term results. The incidence of the side effects although mild was much higher with intravesical BCG therapy. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.74-77